(untitled) (Research, Society and Development, 2018)
Studying the History of Early Childhood Education allows us to establish relationships with the history of childhood and children and to understand the pedagogical conceptions that underlie educational proposals and practices directed at children from zero to six years of age. In this sense, the present article approaches how the process of implantation of the Aurea Barros Kindergarten in the Municipality of Natal / Rio Grande do Norte, in the decade of 1930, as well as, seeks to understand the educative practices destined small child. As a theoretical-methodological procedure, we adopt authors who analyze the History of Early Childhood Education, such as Kuhlmann Junior (1998). As criterion of analysis, we support the studies related to the Social History of Childhood (Heywood, 2004) and Cultura Escolar (Julia, 2012), serving as a conductive bias understanding of the school as a space for the production of knowledge, formation habits and civil behavior. As far as methodological procedures are concerned, we focus on historical sources, such as: government messages, educational legislation and newspapers. In this perspective, we consider the historical and social relevance of one of the first educational spaces for the natal child.